Effects of Strength Training and Anabolic Steroid in the Peripheral Nerve and Skeletal Muscle Morphology of Aged Rats - Krause Neto, Walter; Silva, Wellington de A.; Ciena, Adriano P.; Nucci, Ricardo Aparecido Baptista; Anaruma, Carlos A.; Gama, Eliane F. (Frontiers in Aging Neuroscience, 2017)
Thirty male 20-months-old Wistar rats were divided into groups: IC – initial control (n = 6), FC – final control (n = 6), AC – anabolic hormone control (n = 6), ST - strength trained (n = 6) and STA - strength trained with anabolic hormone (n = 6). All groups were submitted to adaptation, familiarization and maximum load carrying test (MLCT). Strength training (6-8x / session with loads of 50 to 100% MLCT, 3x/week and pause of 120 seconds) was performed in ladder climbing for 15 weeks. The administration of testosterone (TP) was performed 2x/week (10 mg/kg) in animals in the AC and STA groups. After the experimental period, animals were euthanized and the tibial nerve and plantaris muscle removed and prepared for electron transmission and histochemistry. To compare the groups we used one-way ANOVA (post hoc Bonferroni), student's t-tests for pre vs post (dependent and independent variables) comparisons and significance level set at p ≤ 0.05. The following significant results were found: a) aging decreased the number of myelinated axon fibers; b) use of isolated TP increased the diameter of myelinated fibers, along with increased thickness of myelin sheath.; c) ST increased area of myelinated and unmyelinated fibers, together with the myelin sheath. These changes made it possible to increase the area occupied by myelinated fibers keeping their quantity and also reduce the interstitial space; d) association of anabolic steroid and ST increased the area of unmyelinated axons and thickness of the myelin sheath. Compared to ST, both strategies have similar results. However, Schwann cells increased significantly only in this strategy.